PENGEMBANGAN MEDIA PENCERDAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA DI KELAS V SD - Maku, Siltiany; Abdulla, Gamar; Isnanto, Isnanto; Arif, Rifda Mardian; Arifin, Vicka Muniati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop interactive learning media called. Pencerdas to improve the understanding of fifth grade elementary school students on the human digestive system material. This development research adopts the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which involves five systematic stages: needs analysis, media concept design, prototype development, classroom implementation, and final evaluation. The subjects of the study were 24 fifth grade students of SDN 1 Tilango. At the analysis stage, the researcher identified learning gaps, such as the lack of visual and interactive media, which were then used as the basis for designing media based on images, animations, and interactive quizzes. The validation results by media experts, material experts, and teachers showed a media feasibility level of 93.71% (very feasible category), with the highest assessment in the aspects of novelty, ease of use, and content suitability. The practicality test by students obtained a score of 91.66%, while the teacher gave a score of 90%, indicating that the media is easy to integrate into daily learning. Furthermore, the effectiveness test through a comparison of the pretest (average 52.4) and posttest (average 89.6) produced an N-Gain of 0.75 (high category), proving a significant increase in student understanding. This finding shows that Pencerdas not only meets the theoretical feasibility criteria, but is also applicable and has a positive impact on learning outcomes. This media has the potential to be an innovative solution to overcome the challenges of learning complex material at the elementary level, while supporting the realization of fun and meaningful learning. ABSTRAKPenelitian ini bertujuan mengembangkan media pembelajaran interaktif bernama. Pencerdas untuk meningkatkan pemahaman siswa kelas V SD pada materi sistem pencernaan manusia. Penelitian pengembangan ini mengadopsi model ADDIE (Analysis, Design, Development, Implementation, Evaluation) yang melibatkan lima tahap sistematis: analisis kebutuhan, perancangan konsep media, pengembangan prototipe, implementasi di kelas, dan evaluasi akhir. Subjek penelitian adalah 24 siswa kelas V SDN 1 Tilango. Pada tahap analisis, peneliti mengidentifikasi kesenjangan pembelajaran, seperti kurangnya media visual dan interaktif, yang kemudian dijadikan dasar perancangan media berbasis gambar, animasi, dan kuis interaktif. Hasil validasi oleh ahli media, ahli materi, dan guru menunjukkan tingkat kelayakan media sebesar 93,71% (kategori sangat layak), dengan penilaian tertinggi pada aspek kebaruan, kemudahan penggunaan, dan kesesuaian konten. Uji kepraktisan oleh siswa memperoleh skor 91,66%, sementara guru memberikan skor 90%, yang mengindikasikan media mudah diintegrasikan dalam pembelajaran sehari-hari. Selanjutnya, uji efektivitas melalui perbandingan pretest (rata-rata 52,4) dan posttest (rata-rata 89,6) menghasilkan N-Gain 0,75 (kategori tinggi), membuktikan peningkatan pemahaman siswa secara signifikan. Temuan ini menunjukkan bahwa Pencerdas tidak hanya memenuhi kriteria kelayakan teoritis, tetapi juga aplikatif dan berdampak positif pada hasil belajar. Media ini berpotensi menjadi solusi inovatif untuk mengatasi tantangan pembelajaran materi kompleks di tingkat dasar, sekaligus mendukung terwujudnya pembelajaran yang menyenangkan dan bermakna.